Ntobo Specta: Upaya Pengembangan Ekonomi Kreatif Berbasis Tenun Tradisional melalui Fashion Show dan Bazar UMKM - Ismunandar Ismunandar; Nur Khusnul Hamidah (Manfaat : Jurnal Pengabdian Pada Masyarakat Indonesia, 2026)
Ntobo Specta is a community service program implemented by students of the Community Service Program (KKN) of the Bima College of Economics (STIE) as an effort to support the development of a creative economy based on local potential in Ntobo Village. Ntobo Village is known as one of the centers of traditional weaving craftsmen who are the main source of income for most of the community. However, promotion and marketing of woven products are still limited, so innovative activities are needed to increase the attractiveness and economic value of local weaving. Ntobo Specta activities are packaged in the form of a bazaar for weaving MSMEs and a fashion show made from typical Ntobo woven fabrics involving elementary, middle, and high school students. This activity aims to introduce Ntobo weaving to the wider community, increase the interest of the younger generation in local culture, and open marketing opportunities for weaving MSMEs. The implementation method is carried out through the stages of coordination, activity preparation, event implementation, and evaluation. The results of the activity show that Ntobo Specta is able to be an effective medium for promoting culture and the creative economy. The enthusiasm of the community and participants has a positive impact on increasing the existence of Ntobo weaving as a superior regional product. Furthermore, this activity also stimulates economic growth in the community by increasing awareness of local woven products and expanding the marketing network for MSMEs. Thus, Ntobo Specta is a form of community empowerment that integrates cultural preservation with strengthening the creative economy based on local wisdom.